A abstração e a reflexão - Mário Pedrosa, o crítico como revolucionário - Pedroso, Franklin Espath (1992)
The presentation of Mário Pedrosa's life and work and analysis of his ideas in relation to his concept about art criticism, the role of a critic and his defense of the abstract art in Brazil. This dissertation, based above all in Pedrosa’s texts, is restricted to the fifties and shows the influence and importance of this critic in the course of the arts in Brazil.